Professional methods of assessments in architectural design projects: A focus on the relevant parametric measures in selected Nigerian universities - Aderonmu, P. A. (Cogent social sciences, 2017)
In Architecture, Engineering and other allied professional fields, the methods of assessment has for some decades been parametric. In an effort to carry out assessment for the grading of design works, the students have in many ways been confronted with bias, fear, intimidation, uncertainty, and mistrust from peers, studio teacher-instructors, observers, professional jurors, and other stakeholders involved within the process. The research employed a multi-stage stratified purposive sampling technique in which questionnaire responses were analysed using SPSS with regression analysis. The analysis was used for observations, focus group, and oral interviews. In this study, assessment of parameters and methods of grading employed in the Architectural Design Jury with specific reference to four (4) selected universities in Nigeria was made. Several factors militating against the conduct and ethics of the jury methods were also identified. The results revealed key findings in the four selected schools and each performed differently in terms of some significantly relevant parametric factors such as the Jury Review and Format, the Jury Purpose, Hierarchy and its Inherent Pedagogies, the Jury Objectives and Parameters and the Jury Prospects. The engagement of these parametric measures would empower architecture students, jurors, architect-designers, engineers, educators, builders and other allied professionals to make robust and meaningful decisions to attain design satisfaction for the clients and end-users. From the analysis, a dialogically comprehensive parametric process was identified as fit to proffer pragmatic solutions to address trivialities of the problem and is able to fix in answers to related design issues.